Contact transition control of a flexible structure mounted manipulator - Theeraphong Wongratanaphisan (2018)
A flexible structure mounted manipulator (FSMM) is a robotic system that consists of a rigid manipulator installed on a supporting structure that is not rigid. Another robotic system which possesses similar dynamic characteristics is a micro-macromanipulator(MMM) in which a small (micro) manipulator, considered rigid, is mounted on the tip of a long-reach (macro) manipulator, considered flexible. Designing controllers for a FSMM or MMM is a difficult task as the motion of the flexible structure adds complexity to the system dynamics. It is especially difficult when the FSMM is required to interact with its environment. This paper investigates force control techniques for a FSMM in contact transition phase. Three types of controllers are compared: (1) discontinuous control, (2) impedance control, and (3) robust impedance control. These controllers were implemented and tested on a 2-DOF FSMM lab-scale prototype and their performance evaluated and discussed. © 2009 Springer Science+Business Media, B.V.